Comparison of parents knowledge of bad habits and the severity maloclusion of children in schools with different social levels - Baharuddin M. Ranggang; Riana N. Armedina (Journal of Dentomaxillofacial Science, 2020)
Objective: To knows comparison of the level of knowledge of parents of bad habits and the severity of malocclusion children at school with a different social level, namely Elementary School of Kera-Kera Settlement (SD Inpres Kera-Kera) and Al-Biruni Intgrated Islamic Elementary School of Makassar City (SDIT Al-Biruni Makassar). Material and Methods: The sampling method used is purposive sampling. Measurement of the level of parental knowledge using a questionnaire, the severity of children's malocclusion using the Occlusion Feature Index (OFI) method.Results: In the SD Inpres Kera-Kera, the level of knowledge of parents with Low criteria of 63.6%, the severity of malocclusion of children with a very mild OFI score of 2.3%, mild criteria of 34.1%, medium criteria 59, 1%, and the weight criteria are 4.5%. SDIT Al-Biruni assessment of the level of knowledge of good parents as much as 81.4%, the severity of malocclusion with an OFI score of very mild criteria as much as 5.1%, mild criteria as much as 49.2%, medium criteria 42.4%, and severe criteria as much as 3 4%. Conclusion: There is a difference in the knowledge of parents of SD Inpres Kera-Kera and SDIT Al-Biruni parents. Parent’s knowledge of bad habits and malocclusion at SDIT Al-Biruni Makassar is far better than that of SD Inpres Kera-Kera